The Late Villafranchian Absence of Pigs in Europe. Comment on Iannucci, A. The Occurrence of Suids in the Post-Olduvai to Pre-Jaramillo Pleistocene of Europe and Implications for Late Villafranchian Biochronology and Faunal Dynamics. Quaternary 2024, 7, 11 - Bienvenido Martínez-Navarro; Joan Madurell-Malapeira; Sergio Ros-Montoya; M. Patrocinio Espigares; Guillermo Rodríguez-Gómez; Lorenzo Rook; Paul Palmqvist (Quaternary)
On 2015, after the direct study of the most important Late Villafranchian fossil collections of Europe and Western Asia, including Orce (Spain), Pirro Nord and Upper Valdarno (Italy), Appollonia (Greece), Dmanisi (Georgia) and ‘Ubeidiya (Israel), among others, our team proposed the hypothesis that suids disappeared from Europe during the time span between 1.8 and 1.2 Ma. The implications of our conclusions were significant, the arrival of Early Homo into Western Europe, dated to 1.4 Ma at the site of Barranco León in Orce (Spain), preceded the return of pigs into the continent at 1.2 Ma. This hypothesis has been recently challenged because of the finding of an incomplete metatarsal ascribed to Sus sp., with no clear stratigraphic origin, found in the XIX Century Croizet collection of Peyrolles (France), which is housed in the Natural History Museum, London, together with other weak arguments based on the absence of reliable dating for many Early Pleistocene European sites, and other hypothetical records of pigs, with no real fossil support. We answer all these questions and defend that our 2015 hypothesis is correct.